Metal-Free Synthesis of α-H Chlorine Alkylaromatic Hydrocarbons Driven by Visible Light - Lidia De Luca; Luca Ledda; Andrea Porcheddu; Massimo Carraro; Luisa Pisano; Silvia Gaspa (Molecules)
Chlorination is a widely used strategy at the industrial level. Chlorinated products represent indispensable building blocks in synthetic chemistry. Here, we report the synthesis of benzyl chlorides and α-chloro alkyl arenes, mediated by visible light, starting from variously substituted toluenes and N,N-dichloroacetamide as a chlorinating reagent. This methodology is a valid alternative to the syntheses previously reported in the literature. It is a metal-free process and does not involve the use of additives or radical initiators.